An Analysis of the rural dental health services in the province of Bulacan. - Marquez, Eleuteria Sinsioco
This study was an analysis and evaluation of the rural dental health services in the province of Bulacan to determine the extent to which the ?Standards of the Bureau of Dental Health Services? formulated in 1968 was met. One senior dentist and eight dentists were included in this study. Analysis and evaluation were limited to Organization, Professional, Financial dimensions, and to the fourth level of quality care among children due to limitation of time. A survey form filled by the dentists themselves and by this writer was used to gather information. An additional observation form was used by this writer in observing the activities of the dentists. Sources of data were the dentists themselves, members of the rural health unites, individual records of patients for the year 1968 and observations made by this writer. Collected data were analyzed and evaluation by item with the following results: (4.1) Organization Dimension: ?Far below standard?. Of the four recommended items under this dimension only one dentist attained 75%. The others obtained either 50%, 25% and zero so that the mean percentage attainment was 22%. (4.2) Professional Dimension: ?Far below standard?. Of the four recommended items under this dimension, four dentists attained only one item and the mean percentage attainment was 12.5%. (4.3) Financial Dimension: ?Far below standard?. Of the two recommended items under this dimension, four dentists attained one item and the mean percentage attainment was 25%. (4.4) Fourth Level of Quality Dental Care Among Children.: ?Far below standard?. Not one of the eight dentists attained the specified complete dental care treatment for 60% of children 3-14 years old in their respective communities.